2008
DOI: 10.1103/physrevlett.100.067201
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of Magnetoresistance in Organic Semiconductors

Abstract: We report that organic semiconductors such as -sexithiophene (-6T) have magnetoresistance (MR) with unexpected sign changes; depending on applied voltage, temperature, and layer thickness, the resistance may either increase or decrease upon application of a small magnetic field (<100 mT). We propose that MR and the inversion of MR are due to the role of hyperfine interaction in a magnetic field, as illustrated by the recombination-limited regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
111
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(119 citation statements)
references
References 24 publications
5
111
1
Order By: Relevance
“…Additionally, contemporary OMAR models have not been able to explain the positive LFE and HFE in the MC with a single mechanism. With respect to the origin of the MC(V ) trend, multiple suggestions have been made, 6,28,33,34 but none have succeeded in giving a full quantitative description. Therefore, we have constructed a quantitative trion model with all previous reasoning in mind.…”
Section: Trion Modelmentioning
confidence: 99%
“…Additionally, contemporary OMAR models have not been able to explain the positive LFE and HFE in the MC with a single mechanism. With respect to the origin of the MC(V ) trend, multiple suggestions have been made, 6,28,33,34 but none have succeeded in giving a full quantitative description. Therefore, we have constructed a quantitative trion model with all previous reasoning in mind.…”
Section: Trion Modelmentioning
confidence: 99%
“…19 Hu et al 14 observed the negative MC response when the triplet exciton-charge reaction in the active layer dominates the generation of the current in a charge-unbalanced device, because of the reduced interaction between triplet excitons with the excess charges by an external magnetic field. 14 Modulating the dissociation of the excited states (positive MC component) and triplet exciton-charge reaction (negative MC component) by the applied magnetic field, changes the sign of MC curves.…”
Section: Introductionmentioning
confidence: 99%
“…a Author to whom correspondence should be addressed; electronic mail: guotf@mail.ncku.edu.tw The sign of MC curves can be either positive or negative by varying the device structures, 14,15 active materials, 16 and experimental conditions, such as illumination, 17 external bias voltage, 18,19 and temperature. 19 Hu et al 14 observed the negative MC response when the triplet exciton-charge reaction in the active layer dominates the generation of the current in a charge-unbalanced device, because of the reduced interaction between triplet excitons with the excess charges by an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, magnetically changing charge density becomes a practical method to generate MC, leading to density-based MC in fluorescent organic semiconductors. 1,[13][14][15] More specifically, there are two channels, namely, dissociation and charge-reaction, to generate density-based MC. In dissociation channel, an applied magnetic field can increase the singlet ratio in polaron-pair states through intersystem crossing.…”
mentioning
confidence: 99%
“…7-12) or density-based MC. 1,[13][14][15] In mobility-based MC, organic semiconductors need to have spin-spin interaction between charge carriers during transport. Applying magnetic field can disturb this spin-spin interaction through magnetic scattering and, consequently, modifies charge mobilities, generating mobility-based MC.…”
mentioning
confidence: 99%